1984
DOI: 10.1113/jphysiol.1984.sp015472
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of secretin‐stimulated pancreatic secretion in dogs.

Abstract: SUMMARY1. The effect ofthe periodic interdigestive activity of the gut on secretin-stimulated pancreatic secretion was studied in eight conscious dogs each with a Thomas duodenal fistula, a gastric fistula and a Heidenhain pouch.2. Pancreatic water and bicarbonate responses to a small dose of secretin were greatly augmented in phase with the spontaneous periodic activity of the gut. This augmentation was closely related to pancreatic protein secretion.3. As the dose of secretin was increased the interval betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Others have confirmed these findings. [5][6][7] Tanaka and Sarr 8 reported that duodenectomy disrupts not only the coordination of gastric and intestinal migrating motor complexes (MMC) but also the coordination between interdigestive motility and pancreatic secretion, and it abolishes the interdigestive cyclic variations in plasma motilin and pancreatic polypeptide (PP) levels. 9 The release of PP appears to be regulated by a complex interplay between neural input (from the vagus) and humoral factors that originate from the upper gut.…”
Section: Discussionmentioning
confidence: 99%
“…Others have confirmed these findings. [5][6][7] Tanaka and Sarr 8 reported that duodenectomy disrupts not only the coordination of gastric and intestinal migrating motor complexes (MMC) but also the coordination between interdigestive motility and pancreatic secretion, and it abolishes the interdigestive cyclic variations in plasma motilin and pancreatic polypeptide (PP) levels. 9 The release of PP appears to be regulated by a complex interplay between neural input (from the vagus) and humoral factors that originate from the upper gut.…”
Section: Discussionmentioning
confidence: 99%
“…the period of quiescence with no spiking activity (NSA) in the duodenal migrating myoelectric complex (MMC), and secretion increased intermittently before or during phase III, the period of regular spiking activity (RSA), concomitant with plasmal elevations of motilin, gastrin and pancreatic polypeptide (PP). The periodic secretory patterns were interrupted for several hours by feeding ) and were influenced by exogenous secretin, pentagastrin and CCK-8 (Magee & Naruse, 1984, 1988Thor, Laskiewicz, Konturek & Konturek, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The present study has shown that in the fasting dog as much as 50% of the observed maximal protein response to CCK-8 is spontaneously secreted from the pancreas, though the peak volume is less than 10 % of the maximum (Magee & Naruse, 1984). The average protein secretion in one cycle was about 17 % of the maximum.…”
Section: Discussionmentioning
confidence: 83%
“…The periodicity of basal secretion and neural activity of the pancreas, associated with gastroduodenal motility, has been unrecognized or ignored until recently (Magee & Naruse, 1983). Fluid and bicarbonate responses to physiological doses of secretin are potentiated by spontaneous periodic neural activities (Magee & Naruse, 1984). The peak pancreatic bicarbonate response to a fixed dose of secretin can be 18-7 times as much as the nadir response and the potentiation is completely blocked by atropine or ganglionic blockade.…”
Section: Introductionmentioning
confidence: 99%